Predictors of prolonged length of hospital stay and in-hospital mortality among adult patients admitted at the surgical ward of Jimma University medical center, Ethiopia: prospective observational study - Gosaye Mekonen Tefera; Beshadu Bedada Feyisa; Gurmu Tesfaye Umeta; Tsegaye Melaku Kebede (Taylor & Francis Group, 2020)
Background Data regarding prolonged length of hospital stay (PLOS) and in-hospital mortality are paramount to evaluate efficiency and quality of surgical care as well as for rational resource utilization, allocation, and administration. Thus, PLOS and in-hospital mortality have been used as a surrogate indicator of satisfactory treatment outcome and efficient utilization of resources for a given health institution. However, there was a scarcity of data regarding these issues in Ethiopia. Therefore, this study aimed to assess treatment outcome, length of hospital stay, in-hospital mortality, and their determinants. Methods Health facility-based prospective observational study was used for three consecutive months among adult patients hospitalized for the surgical case. Socio-demographic, clinical history, medication history, in-hospital complications, and overall treatment outcomes were collected from the medical charts' of the patients, using a checklist from the day of admission to discharge. PLOS is defined as hospital stay > 75th percentile (≥33 days for the current study). To identify predictor variables for both PLOS and in-hospital mortality, multivariate logistic regression was performed at p-value < 0.05 using SPSS version 20. Written informed consent was sought and secured. Results Of 269 study participants, 91.8% were improved and discharged. PLOS was recorded in 25.3%; at least 33 days of hospital stay. Overall in-hospital mortality was 4.8%; which is equal to an incidence rate of 0.00193 per person-days, 5.2% in-hospital sepsis, and 2.6% of Hospital-acquired pneumonia (HAP), during their hospital stay. After adjusting for other factors; female gender (p = 0.003), emergency admission (p = 0.015), presence of Poly-pharmacy (p = 0.017), and presence of sepsis (p = 0.006) were found to be independent predictors for in-hospital mortality. On top of this, female gender (p = 0.026), patients who was paid by government (p = 0.007), burn-related surgery (p = 0.049), presence of cancer (p = 0.027), > 2 antibiotic exposure (p < 0.0001), and waiting for surgery for > 7 days (p < 0.0001) were independent predictors for PLOS. Conclusion In-hospital mortality rate was almost comparable to reports from developing countries, though it was higher than the developed countries. However, the length of hospital stay was extremely higher than that of reports from other parts of the world. Besides, different socio-demographic, health facility's and patients' clinical conditions (baseline and in-hospital complications) were identified as independent predictors for both in-hospital mortality and PLOS. Therefore, the clinician and stakeholders have to emphasize to avoid the modifiable factors to reduce in-hospital mortality and PLOS in the study area; to improve the quality of surgical care.